5(-6+1)-4n=-5+2n

Simple and best practice solution for 5(-6+1)-4n=-5+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-6+1)-4n=-5+2n equation:


Simplifying
5(-6 + 1) + -4n = -5 + 2n

Combine like terms: -6 + 1 = -5
5(-5) + -4n = -5 + 2n

Multiply 5 * -5
-25 + -4n = -5 + 2n

Solving
-25 + -4n = -5 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
-25 + -4n + -2n = -5 + 2n + -2n

Combine like terms: -4n + -2n = -6n
-25 + -6n = -5 + 2n + -2n

Combine like terms: 2n + -2n = 0
-25 + -6n = -5 + 0
-25 + -6n = -5

Add '25' to each side of the equation.
-25 + 25 + -6n = -5 + 25

Combine like terms: -25 + 25 = 0
0 + -6n = -5 + 25
-6n = -5 + 25

Combine like terms: -5 + 25 = 20
-6n = 20

Divide each side by '-6'.
n = -3.333333333

Simplifying
n = -3.333333333

See similar equations:

| 24=-3(t+-24) | | 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s | | -4b+20=-18-b-19 | | -10j=19-11j | | 5n-6=6n+11 | | 2(22-8)=22+6 |

Equations solver categories